Paleostress Analysis of Chia Gara Structure in Dohuk Area, Northern Iraq - AL- Hachem, Atheer E. K. (Iraqi Journal of Science, 2020)
The use of Right dihedral method, Lisle graph, and Mohr diagram allows the analysis of the paleostress. Fault slip data were measured for eighteen data of two stations located within Chia Gara structure in Dohuk area in the High Folded Zone, Northern Iraq. Depending on Mohr diagram, Bott equation, and vertical thickness, the magnitudes of the paleostress at the time of the tectonic activity were determined. Firstly, Georient Software was used to estimate the orientation of the paleostresses (σ1, σ2 and σ3). Secondly, using the rupture –friction law, taking into account the depth of the overburden, the vertical stress (σv) was calculated to determine the magnitude of the paleostresses in the study area. The values in station one (hinge area, eight data) were σ1=7100, σ2=4121.5, and σ3=1143 bars, whereas the values in station two (the north limb of structure, ten data) were σ1=3740, σ2=1585, and σ3=570 bars. The high magnitudes of the principal stress axes may refer to the active tectonic events which led to the deformation of the area during the Mesozoic Era and the Tertiary period. The study area shows the existence of two types of the faults, the first type is the reactivated faults, the poles of which lie between the sliding line and Mohr envelope. The second type is the inactive faults, with poles lying on the great circle of Mohr diagram